A competitividade da produção de biodiesel no Brasil: uma análise comparativa de mamona, dendê e soja - César, Aldara da Silva (2012)
The possibility of broadening raw material sources for biodiesel production benefits the Brazilian competitiveness. However, the present costs of biofuel production worldwide are not competitive enough if compared to mineral energy. Nowadays, to consider only issues related to the economic aspect, in order to justify the operation of a system, is a practice that has been questioned. The changes in the costumer s actions, production s standard and assessment of social and environmental aspects, by means of the society and the market, have led to an expansion of the dimensions of companies performance analysis and its production connected spaces. Therefore, this thesis proposes to analyze the competitiveness and the main governance structures in productive chains present in the biodiesel sector in Brazil, from three raw materials sources: castor, palm oil and soy. The present work reports the outcomes of a multi-case study, employing techniques of exploratory research literature and documents, and interviews with agents associated in the biodiesel sector. Three main governance structures are highlighted in this analysis: partial vertical integration with small farmers (for all raw materials concerned); the possibility of complete vertical integration of palm oil plantations to the mills; and finally, the purchase of soybeans via spot market. This research illustrates that the biodiesel production of castor bean is impracticable in Brazil in the short term, and it seems to be a future possibility of difficult viability. On the other hand, the palm oil seems to be a viable possibility in the medium-term. It could be possible to develop a chain based on palm oil, and consequently, encourage productive inclusion of small farmers in the North of the country. In contrast to the other resources exposed here, the soybeans revealed significant competitive advantages that have made it possible to fulfill - in quantity - not only the national demand, but also the requirements imposed by the legislation of the Social Fuel Seal and the legislation of the biofuel addition to diesel. The findings of the National Program for Production and Use of Biodiesel (PNPB), related to the productive inclusion of small farms, are still insubstantial, and the institutional environment becomes crucial to the inclusion of family farmers in the biodiesel sector.